How do smartphones affect physical and mental health - Foryś, Angelika; Stawska, Weronika; Miłek, Magdalena; Banach, Mariola; Kwaśniak, Ksenia; Ślusarczyk, Monika; Magierska, Agata; Niemczyk, Anna; Kotowicz, Zuzanna; Kmiotek, Weronika (Quality in Sport, 2024)
Introduction and the aim of the study: Fast technology makes the use of mobile phones global. On one hand, it offers a wide range of opportunities, such as improved interpersonal communication, quick access to information and entertainment, on the other- it may have a negative impact on physical activity or mental well-being. The aim of this study is to summarize the current state of knowledge about the relationship between problems related to smartphone use and health. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the key words: “smartphone addiction”, “mental health” in appropriate configurations. The analysis encompassed data from 39 scientific references published between 2014 and 2024. Conclusions: Problematic smartphone use is a rapidly developing phenomenon, whereas mental health deviance may pose as a risk factor as much as an effect of smartphone overuse. Research results are needed to better describe this disorder and its medical consequences.